Proteasome-dependent protein quality control of the peroxisomal membrane protein Pxa1p - Devarajan, Srishti; Meurer, Matthias; Roermund, C. W. T. van; Chen, X.; Hettema, E. H.; Kemp, S.; Knop, Michael; Williams, C. (Biochimica et biophysica acta. Biomembranes, 2020)
Peroxisomes are eukaryotic organelles that function in numerous metabolic pathways and defects in peroxisome function can cause serious developmental brain disorders such as adrenoleukodystrophy (ALD). Peroxisomal membrane proteins (PMPs) play a crucial role in regulating peroxisome function. Therefore, PMP homeostasis is vital for peroxisome function. Recently, we established that certain PMPs are degraded by the Ubiquitin Proteasome System yet little is known about how faulty/non-functional PMPs undergo quality control. Here we have investigated the degradation of Pxa1p, a fatty acid transporter in the yeast Saccharomyces cerevisiae. Pxa1p is a homologue of the human protein ALDP and mutations in ALDP result in the severe disorder ALD. By introducing two corresponding ALDP mutations into Pxa1p (Pxa1MUT), fused to mGFP, we show that Pxa1MUT-mGFP is rapidly degraded from peroxisomes in a proteasome-dependent manner, while wild type Pxa1-mGFP remains relatively stable. Furthermore, we identify a role for the ubiquitin ligase Ufd4p in Pxa1MUT-mGFP degradation. Finally, we establish that inhibiting Pxa1MUT-mGFP degradation results in a partial rescue of Pxa1p activity in cells. Together, our data demonstrate that faulty PMPs can undergo proteasome-dependent quality control. Furthermore, our observations may provide new insights into the role of ALDP degradation in ALD.
Gesehen am 23.01.2026